Irregularity Measures for Benzene Ring Embedded in P-Type Surface. (26th August 2020) - Liu, Yun; Siddiqa, Aysha; Chu, Yu-Ming; Azam, Muhammad; Basra, Muhammad Asim Raza; Rehman Virk, Abaid Ur
Abstract : A topological index is an important tool in predicting physicochemical properties of a chemical compound. Topological indices help us to assign a single number to a chemical compound. Drugs and other chemical compounds are frequently demonstrated as different polygonal shapes, trees, graphs, etc. In this paper, we will compute irregularity indices for the benzene ring embedded in a P-type surface B R p and the simple bounded dual of the benzene ring embedded in a P-type surface S B R p .